Observations on the Decisions of the Higher Council for the Armenian Language (Vocabulary and Grammar) - AVETISYAN, YURI (Bulletin of Yerevan University B: Philology, 2021)
The shifts in the vocabulary and the grammatical system of modern Armenian presume the necessity of reconsidering and reestablishing the decisions in these fields, and working out and establishing the development of new draft decisions on separate new realities.
Keywords: terminology, shifts, vocabulary, foreign words, Armenian equivalents, clarifiy, regulation, declension forms, uniformity